REST API Architecture Design on Multi-Platform Device Development - Yuda Syahidin; Randy Ramadhan (Jurnal E-Komtek (Elektro-Komputer-Teknik), 2021)
Multi-platform devices are becoming the standard technology in software development. However, the problem of multi-platform is that it must provide a single parent data source, so there is a good relationship between users of multi-platform devices and servers. REST APIs are the best choices that bridge the servers and multiple platforms. That way, the use of REST APIs will be very beneficial, both in terms of servers and platforms as consumption. This research planned to create a REST API architecture that can run in multi-platform with testing techniques using black boxes through postman software. As the basis for making REST APIs, it is better to understand the Architecture of REST APIs, especially REST APIs as a multi-platform device.